Synergic effects of cellulose nanocrystals and alkali on the mechanical properties of sisal fibers and their bonding properties with epoxy - Zhang, Z.; Li, Y.; Chen, C.
Cellulose nanocrystal (CNC), as a new promising nanomaterial, has attracted considerable attention in recent years. In this research, electrophoretic deposition (EPD)was employed to modify sisal fibers with CNCs. Sisal fibers were treated with alkali before CNCs were deposited on their surface. The synergic effects of alkali and CNCs on the mechanical properties of sisal fiber and its interfacial properties with epoxy resin over a range of temperatures were investigated. The results showed that a 62 percent increase in tensile modulus of sisal fibers was obtained. At room temperature, the CNCs coating did not show any obvious effect on the interfacial shear strength (IFSS)between sisal fiber and epoxy while changing the debonding mode with an increased debonding frictional force. In the case of being at elevated temperatures, the CNCs modification significantly reduced the inverse effect of temperature on IFSS owing to the formation of an interphase with improved thermo-mechanical stability.
Keywords: NATURAL FIBERS; NANOPARTICLES; MECHANICAL PROPERTIES; FIBER/MATRIX BOND